Simulation Models for the Evaluation of Investment Projects - Delgado Tello, Pelayo (2019)
The simulation model is a useful assessment tool to analyze in depth evaluation of investment projects, improving investor decision making. Contributes to investigate new project ideas and help identify investment opportunities aimed at the reformulation of projects, adapting to the attitudes and investor requirements. An alternative choice is the mathematics expectation that is used in the calculation of probabilities that an event occurs. The fact that a good estimate of the elements involved in the calculation of profitability is not conducted, can lead to invalidate the analysis, and therefore, can lead to approve unprofitable projects and vice versa. When is known the probability of an event occurring certain number of years, usually applies a certain percentage during that period. For example, if the probability of an event occurring is 20 years, a rate of 5% per annum will apply.